The "Fork-in-the-road" clause - Mitrić Savić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Parties can use arbitration agreement to widen the jurisdiction of the arbitration tribunal, or to narrow it down. Arbitration agreements that embed the so called “fork in the road” clause prevent investors to use multiple dispute resolution mechanisms provided in the agreement. In other words, by initiating proceedings, the investor has made an irrevocable choice. That being said, investors are often drawn into proceedings in the host state, however, not every appearance before domestic courts will constitute a choice under the “fork in the road” clause. Arbitration tribunals have made out criteria under which it will be considered that the investor has chosen a path. The investor will be precluded from initiating arbitration if he has previously tried to resolve the same dispute before domestic courts. Another condition that has to be met cumulatively is that the same parties were involved in the domestic proceedings and in international arbitration, i.e. there must be identity of the parties to the dispute. The parties often opt to include the “fork in the road” clause in arbitration agreements. Serbia has included this clause in majority of its bilateral investment.